2(x-6)+3=-3(4-x)

Simple and best practice solution for 2(x-6)+3=-3(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)+3=-3(4-x) equation:


Simplifying
2(x + -6) + 3 = -3(4 + -1x)

Reorder the terms:
2(-6 + x) + 3 = -3(4 + -1x)
(-6 * 2 + x * 2) + 3 = -3(4 + -1x)
(-12 + 2x) + 3 = -3(4 + -1x)

Reorder the terms:
-12 + 3 + 2x = -3(4 + -1x)

Combine like terms: -12 + 3 = -9
-9 + 2x = -3(4 + -1x)
-9 + 2x = (4 * -3 + -1x * -3)
-9 + 2x = (-12 + 3x)

Solving
-9 + 2x = -12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-9 + 2x + -3x = -12 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-9 + -1x = -12 + 3x + -3x

Combine like terms: 3x + -3x = 0
-9 + -1x = -12 + 0
-9 + -1x = -12

Add '9' to each side of the equation.
-9 + 9 + -1x = -12 + 9

Combine like terms: -9 + 9 = 0
0 + -1x = -12 + 9
-1x = -12 + 9

Combine like terms: -12 + 9 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 6x-12y=72 | | y=-7+5y | | 6x-16-3x=5x-9 | | 2-b+7b-2= | | 8.9y-7.35=12.4y | | 3-6x=-2x-37 | | 6+.10x=0.15x+8 | | -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= | | -6x-76=98-12x | | -1+6x=3x-19 | | (27p^6)^(5/3) | | -6-k+2-5k= | | 8x-2(x-8)=6(x+1)+7 | | 5-10t=-25 | | 40=5x+2(-x+2) | | x^2-23x=3 | | -2y+9-y=-7y-7 | | y/6-4=6 |

Equations solver categories